Implementation of Extreme Poverty Alleviation Policies Based on Data Credibility in Bojonegoro Regency - Prasetijo, Kusnandaka Tjatur; Handoko, V Rudy; Rupiarsieh; Wulandari, Septi (Advances in Social Sciences Research Journal, 2025)
This research seeks to examine the implementation of extreme poverty alleviation policies in Bojonegoro Regency through the lens of Matland’s policy implementation theory. It emphasizes identifying the factors influencing the effectiveness of these policies across three key dimensions: policy substance, implementation processes, and normative legitimacy. The research method is descriptive qualitative, with data collected through policy document analysis, stakeholder interviews, and field observations. The findings reveal that the extreme poverty reduction program in Bojonegoro has improved targeting accuracy by more accurately identifying extreme poor families, which was done through the application of data pattern analysis and feature extraction from household data. However, weaknesses were found in the procedures and coordination mechanisms between stakeholders at the village and sub-district levels, which hindered optimal program implementation. The findings of this research resulted in a policy implementation model adapted from Matland’s theory, where the substance aspect of the policy (targeting data on poor households) was successfully strengthened through the use of data technology, which is a novelty of this research, while the procedural aspect (coordination mechanism) requires improvement to make the policy implementation more efficient.